TURKISH WOMEN: THOSE WHO ARE EXPOSED TO VIOLENCE AND THOSE WHO ARE NOT EXPOSED TO VIOLENCE - Gundogdu, Rezzan; Yavuzer, Yasemin (European Scientific Journal, ESJ, 2013)
The aim of this study is to determine what kind of violence women are exposed to, the reason why they are exposed to violence, the effects of the violence exposed on women, how they perceive violence and to study the opinions of women who are exposed and who are not exposed to violence in what concerns their marriages, their expectations from life and their way of living. This qualitative research was carried out in the descriptive model. The population of this study is women living in the city of Aksaray-Turkey. In the research, the qualitative data collection technique of interviewing was employed. In the research, in-depth interviews were conducted with a total of 68 women (34 who were subjected to violence and 34 who were not). Each of the interviews has been carried out by the researcher and lasted around 30-40 minutes. The findings of the present study conclude that marriage by family decision, whose husband’s high use of alcohol and cigarettes and not knowing the legal rights are the risk factors for physical domestic violence in Turkey. As an another finding of the study, we determined similar results in the following variables for women in the both groups; their levels of education, their husbands’ levels of education, their employment status, their everyday lives, family activities and their expectations from the future. However, there were differences in terms of their hobbies and limitations put by their husbands.